Character Building Efforts Through Religious Song Media for Elementary School Students - Devi, Rista Apriliya (International Research-Based Education Journal, 2023)
The purpose of this study is to describe the lyrics of children's songs used in the fifth grade of SD 1 Muhammadiyah Temanggung, Central Java. in the effort of Islamic Character Building. The research method used is descriptive qualitative. Data analysis is inductive/qualitative, and qualitative research results emphasise meaning rather than generalisation.  This research was conducted in class V of SD Muhammadiyah Temanggung. Central Java. This research was conducted from November to December 2022.  The data collected were the results of interviews, literature review, and documentation. The results of this study indicate that religious song lyrics have an important role in efforts to build students' Islamic character. The song taught to fifth grade students of SD 1 Muhammadiyah Temanggung already fulfils Islamic character values.  The songs taught are easy to sing, easy to memorise and in accordance with the characteristics of students. In an effort to form Islamic character values in fifth grade students of SD 1 Muhammadiyah Temanggung. Religious values are already found in every lyric of the song "Sepohon Kayu".